2013
DOI: 10.1007/s00209-013-1236-8
|View full text |Cite
|
Sign up to set email alerts
|

Decomposable and indecomposable algebras of degree $$8$$ 8 and exponent 2

Abstract: Abstract. We study the decomposition of central simple algebras of exponent 2 into tensor products of quaternion algebras. We consider in particular decompositions in which one of the quaternion algebras contains a given quadratic extension. Let B be a biquaternion algebra over F ( √ a) with trivial corestriction. A degree 3 cohomological invariant is defined and we show that it determines whether B has a descent to F . This invariant is used to give examples of indecomposable algebras of degree 8 and exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 24 publications
2
33
0
1
Order By: Relevance
“…1]. Hence, Merkurjev's Chow group computations in [10,Theorem 6.7] show that the scalar extension map This theorem allows to construct an example of a biquaternion algebra with nontrivial invariant over a field of 2-cohomological dimension 3: By Theorem 4.1, every indecomposable algebra of degree 8 and exponent 2 can be scalar extended to an indecomposable algebra over a field of cohomological 2-dimension 3. Since indecomposable algebras of degree 8 and exponent 2 exist, they exist also over fields M with cd 2 (M) = 3.…”
Section: Indecomposable Algebras In Cohomological Dimensionmentioning
confidence: 98%
See 2 more Smart Citations
“…1]. Hence, Merkurjev's Chow group computations in [10,Theorem 6.7] show that the scalar extension map This theorem allows to construct an example of a biquaternion algebra with nontrivial invariant over a field of 2-cohomological dimension 3: By Theorem 4.1, every indecomposable algebra of degree 8 and exponent 2 can be scalar extended to an indecomposable algebra over a field of cohomological 2-dimension 3. Since indecomposable algebras of degree 8 and exponent 2 exist, they exist also over fields M with cd 2 (M) = 3.…”
Section: Indecomposable Algebras In Cohomological Dimensionmentioning
confidence: 98%
“…In [10], the invariant δ was associated to any biquaternion algebra B over K where K/F is a quadratic field extension and char(F) 2. It was shown that the invariant is trivial exactly when B has a descent to F. This invariant proved to be a refinement of an invariant ∆ defined in [16,Section 11] for algebras of degree 8 and exponent 2, which is trivial when the algebra decomposes and is conjectured to be nontrivial otherwise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By [5] the induced pullback on T -equivariant Chow groups CH T (pt) → CH T (U ) is an isomorphism. Since CH T (U ) ≃ CH(U/T ) ≃ CH(U/B) and CH T (pt) can be identified with the symmetric algebra Sym(T * ) of the group of characters of T , it gives an isomorphism (1) c CH : Sym(T * )…”
Section: Semi-decomposable Invariants and The Chow Groupmentioning
confidence: 99%
“…As observed above, this is not true anymore in higher degree. More generally, if A is of degree 8 and exponent 2 and F ( √ d) ⊂ A is a quadratic field extension, there exists a cohomological criterion associated with the centralizer of F ( √ d) in A which determines whether F ( √ d) lies in a quaternion F -subalgebra of A (see [Ba,Prop. 4.4]).…”
Section: Introductionmentioning
confidence: 99%